Technology of bibliographic descriptions conversion - Касілов, Олег Вікторович; Суботіна, Альона Валеріївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the development of the technology of conversion of bibliographic descriptions from the older formats into the current State Standard 7.1:2006 since there is no such possibility in the existing control systems of bibliographic information. The main objective is to study the structure of bibliographic descriptions of different standards and to develop the principles of conversion of bibliographic descriptions into the current format, and the algorithm of the system operation for their preparation. The use of modern automated means of processing of bibliographic information increases the efficiency, and reduces the large number of routine operations and the time spent. The article examines the structure of bibliographic descriptions, compares and analyzes the differences in the State standards 7.1-84 and 7.1:2006. This information is used to form the principles of the transformation on the example of the abstract of a dissertation. The presented method allows automating and improving the process of transformation from the old to the current standards. The method and the developed algorithm are not unique to the abstract, and can be used for other documents, with some modifications. It was proposed to use XML for the markup of bibliographic description on the basis of a certain set of rules. The research results can be applied by bibliographers, librarians and others involved in the analytic-synthetic processing of information, and integrated into the national library systems or web-resources